Comparative Study of Feto-Maternal Outcome of Antenatal Cases as per the Standard WHO Guidelines vs Revised Antenatal Visit Schedule during COVID 19 Pandemic - Bhardwaj, Bikram; Menon, Aruna; Prajapati, Vipin Kumar; Kathi, Apphia Saphir; Singh, Randeep (Journal of Maternal and Child Health, 2023)
Background: Good antenatal care helps a woman face labour in good health and optimum conditions. The National Institute for Health and Care Excellence (NICE) and WHO guidelines suggest 15 visits in the whole pregnancy. Keeping in view the COVID-19 pandemic to reduce the exposure of pregnant ladies the number of antenatal visits was reduced to 7 milestone visits and outcome was noted. This study aimed to do a comparative study of feto-maternal outcome in antenatal cases at our centre using standard WHO protocol vs. revised antenatal protocol during COVID-19 pandemic. Subjects and Method: This was an observational study done at a tertiary care center of an Armed forces hospital with target population as pregnant ladies attending antenatal care Out patient department of the hospital during COVID19 pandemic Vs Antenatal cases in previous 1 year. A comparative analysis of pregnancy outcome, maternal variables during pregnancy and delivery along with neonatal variables was done. Results: There were lesser deliveries by 41.7% as compared to non-COVID times. There was an increase in the caesarean delivery rate and instrumental delivery rate during COVID times by 11% and 53% respectively. There was increase in Vaginal birth after caesarean (VBAC) by 26.6%. The incidence of fetal growth restriction, placental abruption, maternal anaemia and gestational diabetes mellitus, oligohydramnios and polyhydramnios was low. The incidence of spontaneous abortions was also low in our study. In contrast, the incidence of pre-term deliveries doubled from 7.4% to 13.4%. Neonatal morbidity and mortality indicators like Neonatal Intensive care unit (NICU) admissions showed a rising trend of 1.7% during the COVID (14.6% to 16.3%) with a minimal rise in early neonatal deaths by 0.2%. Conclusion: Our model doesn’t show an increase in maternal, neonatal morbidity, and mortality. This model can be used as a standard of care for Antenatal patients during Pandemics. It reduces the risk exposure of the gravid mother without any significant increase in maternal and neonatal morbidity and mortality. Keywords: antenatal care, COVID-19 pandemic, revised antenatal schedule. Correspondence: Vipin Kumar Prajapati. Graded Specialist Department of Obstetrics Gynecology, AFMC, Pune. Email: vipinafmc@gmail.com. Contact No: 8811015130